Optimasi Parameter Proses 3D Print Produk Kopling Menggunakan Filamen PLA (Polylactic Acid) dan Response Surface Methodology - Nisah, Khairun; Sateria, Angga; Oktriadi, Yudi; Yudo, Eko; S Suzen, Zaldy (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
3D printing technology is one of the latest innovations in the manufacturing industry. One of the uses of 3D printing is manufacturing products and machine components such as making coupling components on the Z axis of a 3D printer machine. 3D printing technology works by extruding thermoplastic filaments to form layers of material gradually. In this research, the filament used is PLA (Polylactic Acid) filament with a diameter of 1.75 mm. This research aims to analyze the effect of process parameters on surface roughness using response surface methodology (RSM). The parameters tested were nozzle temperature (215°C, 230°C, 245°C), layer height (0.2 mm, 0.25 mm, 0.30 mm), and print speed (50 mm/s, 65 mm/s, 80 mm/s). The results showed that nozzle temperature and layer height significantly influenced the surface roughness results. The most optimal process parameters to minimize surface roughness are at nozzle temperature of 249°C, layer height of 0,17 mm, and print speed of 90 mm/s.